Effectiveness Of Improving The Mechanisms Of Training Educational Work In Institutions Of Higher Education - Dilafruz Muhiddinovna Ismoilova (Euro Asian Journal Publishing, 2024)
The article scientifically covers aspects related to determining the level of education of students.
Keywords: morality; humanism; goodness; creativity